Dietary daidzein, but not genistein, has a hypocholesterolemic effect in non-ovariectomized and ovariectomized female Sprague-Dawley rats on a cholesterol-free diet. Issue 9 (2nd September 2017) - Bhattarai, Keshab; Adhikari, Sudhashree; Fujitani, Mina; Kishida, Taro
Abstract: We compared the effects of two major isoflavones, daidzein and genistein, on lipid metabolism in rats. Daidzein (150 mg/kg diet), genistein (150 mg/kg diet), daidzein and genistein (1:1, 300 mg/kg diet), or control diets were fed to 4 groups of 6-week-old ovariectomized (Ovx) and non-Ovx Sprague Dawley rats for 4 weeks. Dietary daidzein, but not genistein, reduced serum and hepatic total cholesterol levels significantly relative to that by the control group, regardless of whether the rats had undergone ovariectomy. Genistein did not exhibit any physiological effects on lipid levels, but did affect genes involved in cholesterol metabolism. These results indicate that daidzein and genistein may influence lipid regulation via differing modes of action. Abstract : : Dietary daidzein, but not genistein, reduced serum and hepatic total cholesterol levels significantly relative to that by the control group, regardless of whether the rats had undergone ovaritectmy.